(untitled) (Nepal Journal of Neuroscience, 2023)
Background: Alcoholism, also known as alcohol use disorder (AUD), is a broad term for any drinking of alcohol that results in mental or physical health problems like anxiety, dependence and depression. The present study was conducted with an aim to determine the association between alcohol dependence and depressive episode before and after treatment for alcohol dependence. Materials and Methods: An observational study was conducted among all diagnosed alcohol dependent and depressed patients aged more than 18 years, attending to Psychiatry OPD of a Medical College in Kolkata for a period of one year. After getting permission from the local ethics body, initial assessment was done on first visit of the patients to the psychiatry OPD with a semi structured questionnaire for socio-demographic profile and using AUDIT, CIWA and HAM-D 17 scale for their mental status. Further assessments were done in between day 14 to day 16, next in between day 30 to day 35 and final assessment was done after 2 months using same scales. Relationship between depression with alcohol dependence were determined by Pearson corelation test and represented in the form of table and scatter plot. Changes in mean score of different scales before and after treatment was assessed by paired t test considering confidence interval (CI) of 95% and p value ≤ 0.05 as significant. Result: Out of 70 patients, almost 90% of them were below the age 45 years with male preponderance (94.3%). Paired t test result showed, association of mean scores of different scales, before and after treatment of dependence was statistically significant (p=0.00). Mean AUDIT score, mean CIWA score and mean HAM score for the patients were found to be decreased with advancement of treatment. Pearson correlation test revealed, moderate relationship between AUDIT score and HAMD17 score (0.522) and strong relationship between AUDIT score and CIWA score (0.789). Conclusion: If alcohol dependence is treated properly there will be automatically decreased prevalence of alcohol withdrawal and alcohol induced depressive episodes.